James Joyce Studies in Dubrovnik - Klepač, Tihana (Array, 2003)
A report on the IUC Dubrovnik course with a presentation of papers by Michael Patrick Gillespie, Austin Briggs, Ellen Carol Jones, Morris Beja, Judith Harriton, Stipe Grgas and Ljiljana Ina Gjurgjan, Morton Levitt, and on the roundtable entitled "Croatian James Joyce" held in memory of Professor Ivo Vidan.